An alarming case of metallic sharp foreign body ingestion in an infant - Malhotra, Sonali (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2023)
Foreign body ingestion is a frequent challenge in the emergency room, with potential morbidity affecting around 1% of patients, often stemming from unintentional incidents. Accidents of this nature can result in severe complications leading to fatalities. Common complications involve lacerations, punctures, abscess formation, perforation, pneumomediastinum, mediastinitis, pneumothorax, pericarditis, tamponade, fistulas, and even vascular injuries to the aorta. The risk escalates significantly when the ingested object is sharp and narrow. Presenting an intriguing case, we report an instance of an infant ingesting a metallic, sharp foreign body. This particular case raises unique challenges given the vulnerability of the infant and the potential for severe complications associated with sharp objects. Immediate and precise medical intervention becomes paramount in such scenarios to prevent adverse outcomes. Vigilance in the emergency room is crucial, as the nature of foreign body ingestion can lead to diverse complications, emphasizing the need for a comprehensive understanding and swift response in managing these cases, particularly when involving infants who are at a heightened risk.